Laparoscopic nephrectomy: analysis of 34 patients - Domingos, André Luis Alonso (2003)
OBJECTIVE: To analyze the clinical experience of laparoscopic nephrectomy for benign and malignant diseases at a university hospital. METHODS: From February 2000 to March 2003, 34 patients (14 men and 20 women) underwent transperitoneal laparoscopic total nephrectomy at the Hospital das Clinicas – FMRP-USP: 28 (82.3%) patients had benign diseases and 6 (17.7%) malignant neoplasias. Benign diseases were represented by: urinary stones (N-9, 32.1%), chronic pyelonephritis (N-8, 28.6%), vesicoureteral reflux (N-4, 14.3%), ureteropelvic obstruction (N-3, 10.7%), multicystic kidney (N-2, 7.1%) and pyonephrosis (N-2, 7.1%). Patients age range was 2-79 years (mean – 35,1 years). RESULTS: In 32/34 patients the procedures were accomplished successfully. In 2 (5.8%) cases of pyonephrosis, open conversion was necessary due to perinephric abscess and difficulties in dissection of renal hilum. Two patients had intraoperative complications (1 duodenum serous laceration an 1 vascular lesion of renal hilum), but both were managed laparoscopically. Two (5.8%) post operative complications (1 delayed bleeding and 1 pancreatic fistula) required open surgical exploration. The mean time of hospital stay was 58h (18 to 240h). CONCLUSION: Laparoscopic nephrectomy proved to be a method safe and associated with a low rate of morbidity, shorter hospital stay and no casualties.